Prevalence and course of mood and anxiety disorders, and correlates of symptom severity in adolescents with type 1 diabetes: Results from diabetes LEAP. Issue 4 (16th March 2021) - Nguyen, Linh Anh; Pouwer, Frans; Winterdijk, Per; Hartman, Esther; Nuboer, Roos; Sas, Theo; de Kruijff, Ineke; Bakker‐Van Waarde, Willie; Aanstoot, Henk‐Jan; Nefs, Giesje
Abstract: Objectives: We aim to determine the prevalence and the course of anxiety and mood disorders in Dutch adolescents (12–18 years old) with type 1 diabetes, and to examine correlates of symptom severity, including parental emotional distress. Methods: Participants were 171 adolescents and 149 parents. The Diagnostic Interview Schedule for Children‐IV was used to assess current, past year and lifetime anxiety and mood disorders in adolescents. Symptom severity and diabetes distress were measured with validated questionnaires. Correlates of these symptoms were examined using hierarchical regression analyses and included demographics (adolescent sex and age), clinical factors (diabetes duration, treatment modality, most recent glycated hemoglobin A1c ; all extracted from medical charts), adolescent diabetes distress, and parent emotional distress. Results: Twenty‐four (14%) adolescents met the criteria for ≥1 disorder(s) in the previous 12 months. Anxiety disorders were more prevalent than mood disorders (13% vs. 4%). Lifetime prevalence of anxiety and mood disorders was 29% ( n = 49). The presence of any of these disorders earlier in life (from 5 years old up to 12 months prior to assessment) was associated with disorders in the past 12 months (OR = 4.88, p = 0.001). Higher adolescent diabetes distress was related to higher symptoms of anxiety ( b = 0.07, p = 0.001) and depression ( b = 0.13, p = 0.001), while demographics, clinical characteristics, and parental emotional distress were not related. Conclusions: Anxiety and mood disorders are common among adolescents and related to earlier disorders. Higher diabetes distress was related to higher symptom severity. Clinicians are advised to address past psychological problems and remain vigilant of these problems.